Educational expansion without equalization: a reappraisal of the 'Effectively Maintained Inequality' hypothesis in children's choice of the upper secondary track. Issue 1 (1st January 2017) - Guetto, Raffaele; Vergolini, Loris
ABSTRACT: Previous studies of trends in social inequalities in upper secondary track choices in Italy found evidence that, in the period of highest educational expansion, horizontal inequalities increased, consistently with the Effectively Maintained Inequality thesis (EMI). Our paper, focusing on the youngest birth cohorts (1958–1989), documents that enrolments at upper secondary schools have become almost universal and have been followed by a huge expansion of the academic track. Although the latter has also involved children from the lowest social strata, our evidence suggests that their relative disadvantage to attend the academic track, compared to the most privileged social groups, has diminished only slightly. When distinguishing between different curricula within the academic track, we found evidence supporting the EMI hypothesis also among recent cohorts: the expansion of the academic track has gone hand-in-hand with increasing social inequalities in the chances to attend more prestigious curricula. Finally, social class inequalities in the chances of enrolling at the academic track are stronger at high levels of parental education, while they are largely muted among low-educated parents. We suggest the latter as a possible mechanism to explain why educational expansion may not produce a decline in the association between social origins and educational attainment.